On the dependence of fluorescence intensity on the concentration of photosensitizer solutions - G. A. Meerovich; I. D. Romanishkin; E. V. Akhlyustina; V. B. Loschenov (Biomedical Photonics, 2025)
When studying the optical properties of photosensitizers, it is assumed that their fluorescence intensity depends linearly on concentration. How- ever, there are many factors that need to be taken into account. At low photosensitizer concentrations, a part of the excitation radiation energy is lost beyond the volume of the excited solution, and due to local or one-directional registration, a large part of isotropically emitted fluorescence radiation is also not registered. At higher concentrations, the loss of fluorescence light increases due to its partial re-absorption by the photosensi- tizer molecules and subsequent isotropic re-emission with quantum yield much lower than 1, and further increase of concentration leads to partial aggregation of PS, and to the following decrease of effective fluorescence. At high absorption, fluorescence is excited only in a limited volume close to the excitation radiation source, leading to higher significance of light registration geometry. This should be taken into account in fluorescence diagnostics and navigation using this characteristic.